2021
DOI: 10.1097/nor.0000000000000790
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dexamethasone in Diabetic Patients Undergoing Primary Total Joint Arthroplasty

Abstract: Dexamethasone reduces postoperative pain and nausea, with no evidence of increased rate of infection in total joint arthroplasty. However, the effects of dexamethasone on diabetic patients undergoing total joint arthroplasty remain relatively unexplored. The purpose of this study was to examine the effects of dexamethasone on postoperative blood glucose levels, prosthetic joint infections (PJIs), and 90-day hospital returns in diabetic patients following total joint arthroplasty. Retrospective analysis was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…The full versions of 41 articles were retrieved after screening and conducting a detailed selection process. Finally 16 articles (Nazar et al 2011;Tien et al 2016;Nazar et al 2009;Corcoran et al 2021a;Backes et al 2013;Purushothaman et al 2018;Zhang et al 2014;Shang et al 2022;Wasfie et al 2018;Herbst et al 2020;Godshaw et al 2019;Allen et al 2020;Egan et al 2019;Harding et al 2021;O'Connell et al 2018;Corcoran et al 2021b) met the inclusion criteria and underwent data extraction. The details of the screening procedure are shown in Fig.…”
Section: Literature Search and Retrievalmentioning
confidence: 99%
See 4 more Smart Citations
“…The full versions of 41 articles were retrieved after screening and conducting a detailed selection process. Finally 16 articles (Nazar et al 2011;Tien et al 2016;Nazar et al 2009;Corcoran et al 2021a;Backes et al 2013;Purushothaman et al 2018;Zhang et al 2014;Shang et al 2022;Wasfie et al 2018;Herbst et al 2020;Godshaw et al 2019;Allen et al 2020;Egan et al 2019;Harding et al 2021;O'Connell et al 2018;Corcoran et al 2021b) met the inclusion criteria and underwent data extraction. The details of the screening procedure are shown in Fig.…”
Section: Literature Search and Retrievalmentioning
confidence: 99%
“…Ten (Nazar et al 2011;Tien et al 2016;Nazar et al 2009;Corcoran et al 2021a;Purushothaman et al 2018;Zhang et al 2014;Shang et al 2022;Wasfie et al 2018;Egan et al 2019;Corcoran et al 2021b), six (Tien et al 2016;Corcoran et al 2021a;Purushothaman et al 2018;Zhang et al 2014;Shang et al 2022;Wasfie et al 2018), nine (Nazar et al 2011;Tien et al 2016;Corcoran et al 2021a;Purushothaman et al 2018;Zhang et al 2014;Shang et al 2022;Wasfie et al 2018;Allen et al 2020;O'Connell et al 2018), six (Tien et al 2016;Corcoran et al 2021a;Shang et al 2022;Egan et al 2019;Harding et al 2021;O'Connell et al 2018) and two (Egan et al 2019;O'Connell et al 2018) studies reported glucose levels at baseline (preoperatively), intraoperatively (in the midterm of surgery), at the end of surgery, on postoperative day 1 (POD 1), and POD 2. The results in the trial by Corcoran TB 2020(Corcoran et al 2021a were split in the forest plot, with Corcoran TB 2020(1) representing the comparison between dexamethasone 4 mg with control, and Corcoran TB 2020(2) representing the comparison between dexamethasone 8 mg with control.…”
Section: Effect Of Dexamethasone On Intraoperative And/ or Postoperat...mentioning
confidence: 99%
See 3 more Smart Citations